Dynamics and Driving Factors of Carbon Storage in the Yellow River Delta from 1980 to 2020 - SUN Hanqing; CUI Buli; JIANG Dejuan; LI Yuan; LUO Yongming (Renmin Zhujiang)
Coastal wetland is one of the most critical ecosystems for mitigating climate change and sequestrating carbon. Detecting dynamic changes in carbon storage of coastal wetland can clearly reveal their carbon sequestration capacity, which is helpful for protecting coastal wetland ecosystems and achieving carbon peaking and neutrality targets. We used the InVEST model supporting by statistical analysis and GIS to investigate carbon storage dynamics and its driving factors in the Yellow River Delta (YRD) for the period of 1980—2020. The results indicated that①carbon storage in the YRD initially increased and then decreased from 1980 to 2020, resulting in an overall decrease from 1.561×107 t to 1.556×107 t, with a maximum loss of 1.310×106 t (-7.8% ) from 1990 to 2020. Specifically, carbon storage increased by 1.3×105 tC/a from 1980 to 1990, decreased by 6.5×104 tC/a from 1990 to 2010, and further decreased by 2.0×103 tC/a from 2010 to 2020. ②Spatially, carbon storage exhibited distinct variations. Low values were primarily observed in tidal flats and wetland area. Medium values were found in the inland extension of wetland, while high values were distributed between the first two areas and along the Yellow River. ③The decrease in carbon storage was mainly attributed to land use conversion from wetland and grassland to built-up area, salt pan, and mariculture. Additionally, the construction of large-scale tidal barriers in the YRD altered the distribution of carbon storage by affecting sea-land hydrological connectivity, vegetation, and soil properties. Notably, carbon storage tended to increase with greater distance from tidal barriers. Overall, promoting the conversion of land use types towards wetland ecological restoration will be crucial for enhancing the carbon sink in the YRD in the future.